Sport Consumption, Fan Engagement, Sport Statistics – Post-specific Passing Characteristics in Football - Marton, Szabolcs; Ráthonyi, Gergely (International Journal of Engineering and Management Sciences, 2022)
Digitalization and the explosive development of technology have led to significant changes in football. Due to the increasing amount of data available through various sensors and other data collections, we can observe the rise of data-centric, analytical and statistically oriented thinking in football, which is also of interest to fans. Digitalisation is also closely linked to sports consumption, which is why we have seen significant changes in this area in recent years. The pandemic has further amplified the speed of digital transformation in the sports industry. One of the most important contents for sports organizations and their fans is the in-depth sports statistics and analysis that enhances the consumer experience. In our study, we examined the most common performance indicator in football, passing. Our goal was to examine the position-specific pass characteristics in detail, therefore we also examined different pass properties in our research. As a model for our analysis, I chose the premier league, which has the highest UEFA coefficient. The three rounds (rounds 30-32) of the championship season 2019/2020 have been recorded and analyzed in terms of passes. there was a significant difference between the average number of passes per game between defensive and offensive players (t=7,988, p